Long-Term Rainfall and Temperature Trends in East Java Under Climate Change - Pujiastuti, Ratih; Suharyanto, Suharyanto; Wulandari, Dyah Ari; Nuramini, Tika Morena (Universitas Diponegoro, 2026)
At present, climate change is a global issue affecting the entire world, including tropical countries such as Indonesia. Previous studies have indicated that changes in these conditions have grave impacts on hydrological disasters. Therefore, the pattern of climate change needs to be analyzed for the feasibility of adaptation and mitigation in the future. This present study developed analyses into the trend in temperature variation over East Java both on an annual and daily time scale. Observation data within a long period from 1985 to 2023 was used for comprehensive results. Methods applied include linear regression, the Man-Kendall test, and Sen's Slope test. The new finding that emerged for the temperature variable was that the increase in temperature went over the global and national averages and consistently showed a significant increasing trend across the study area. However, the rainfall variable revealed different results in highlands, where the rainfall intensity decreased-in SDII and R100, inversely proportional to coastal areas. It means that climate change does not occur uniformly everywhere but varies spatially. These findings raise a case for climate change mapping to formulate appropriate adaptation and mitigation strategies.